Evangelicals incorporated: books and the business of religion in America - Vaca, Daniel (Harvard University Press, 2019)
Finding profit : the ascendance of commercialism -- Brands of distinction: fundamentalist networks and the value of ecumenism -- Trade associating: evangelical allegiance in the mass market -- Righteous retail : women, family, and the social power of selling -- Financial faith: corporate finance and traditions of free enterprise -- The spirit of segmentation: niche markets and the pursuit of diversity.